Hesychast roots of anthropomystical ideas in ukrainian philosophical tradition - Leonid Mozghovyi (Cхід, 2013)
The ways of spiritual development provided by Hesychast ascetic doctrines are conceptually sustained by a paradigm of anthropomystic ideas which bear the traits of mythological thinking and are special forms of interiorization of the fundamental religious concept which is transcendence. In the light of the concept of transcendence mysticism is a crucial phenomenon which can sustain some innovative antropology for the contemporary world. Founded on the works of such famous Orthodox figures as St. Symeon the New Theologian, St. Gregory Palamas, St. Isaac the Syrian, St. Mark the Ascetic, St. John of the Ladder, and others, the concept of integral knowledge has roots in the Orthodox mystical tradition of hesychasm. According to hesychast teaching, man's primary goal is an experiential knowledge of God, which is achieved by "bringing one's mind to one's heart" or by aligning one's mind with the Divine Energies. Guided by hesychast teaching, Russian and Ukrainian thinkers criticize the Western philosophy "to deify" the human mind, reason, and logic. Instead, they see the mind as part of a broader cognitive totality that includes intuition, feeling, and man's overall capacity to apprehend the world. of the main elements of hesychasm is "sober and prayer".Sobriety is associated mental asceticism, with protecting one's mind from agitated and passions.